Pengaruh Model Pembelajaran Kooperatif Tipe Stad Terhadap Keterampilan Berbicara Peserta Didik - M. Adi Kusmayadi; Muhammad Makki; Muhammad Syazali (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2023)
This study aims to determine the effect of the STAD cooperative learning model on the speaking skills of fifth-grade students SDN Pidada for the 2022/2023 academic year. The research method used is a quantitative approach with an experimental design. The experimental design used is an experimental design with a shape nonequivalent control group design. The results of data analysis of students' speaking skills in the experimental class which were given treatment with the STAD learning model underwent changes, the speaking skills acquired by students in the experimental class showed an average value pre-test of 57,552 and the average value post-test of 76,041, while the average value pre-test in the control class of 50,520 and the average value post-test of 57,291. Thus, the cooperative learning model typeStudent Teams Achievement Divisions (STAD) can improve students' speaking skills.